Perceraian dalam Pandangan Keutamaan Kristiani dan Amoris Laetitiae sebagai Manajemen Pendampingan Keluarga - Kurniawan, Jery (Felicitas, 2023)
The Church addresses family as ecclesia domestica or the “household church.” Through this title, the Church wants to emphasize that family has an important role in the formation of the Church. Without family, the Church cannot carry on its traditions. The rapid advancement of technology can change suddenly a longstanding culture that has been built for a long period. In the midst of these changes, most people only focus on their own interests to defend themselves against all existing crises. This situation makes people become individualists. This cultural shift also affects the dynamics within the family. Individualism makes people only think about and prioritize their own desires. This has an impact on human life in achieving happiness, as people only pursue their own pleasure and ignore others. In response to this situation, Pope Francis issued an encyclical entitled Amoris Laetititae. In this encyclical, he discusses his concern about problems faced by families in today’s world. In his appeal, the Pope proposes pre-marital formation to equip candidates who will lead family life. This coaching is considered very important and needs to be prepared properly and precisely. In preparing the pre-marital coaching, a strong management system is required in order to achieve the intended goal of forming today’s families that have a happiness within. As a result, this encyclical can serve as the foundation for the management of family fostering so that family may find happiness in their lives.